Influencer Marketing And E-Wom On Muslim Fashion Buying Decisions On Social-Media: An Extended Tpb Framework - Ismail Pulungan; Nur Rahmi Irfaniah (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2026)
This study aims to analyze the effects of influencer marketing and Electronic Word Of Mouth (e-WOM) on Muslim fashion purchase decisions on social media using the Theory of Planned Behavior (TPB) approach. A quantitative method was employed by distributing an online survey to 240 Muslim female respondents in Jakarta, Yogyakarta, Surabaya, and Bandung. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that influencer marketing and e-WOM have a positive and significant effect on purchase decisions of Muslim fashion on social media. In addition, attitude, subjective norm, and perceived behavioral control also significantly influence purchase decisions. Purchase intention is proven to act as a mediating variable that strengthens the relationship between digital marketing variables and purchase decisions. These findings suggest that Muslim fashion purchase decisions on social media are influenced by both digital marketing factors and consumers’ psychological considerations. This study applies an extended TPB framework by incorporating influencer marketing and e-WOM as external antecedents of purchase intention and purchase decision in the Muslim fashion context.